Sex differences in the central nervous system - Shansky, Rebecca M. (Neuroscience-net reference book series, 2016)
Sex Differences in the Central Nervous System offers a comprehensive examination of the current state of sex differences research, from both the basic science and clinical research perspectives. Given the current NIH directive that funded preclinical research must consider both females and males, this topic is of interest to an increasing percentage of the neuroscience research population. The volume serves as an invaluable resource, offering coverage of a wide range of topics: sex differences in cognition, learning, and memory, sex hormone signaling mechanisms, neuroimmune interactions, epigenetics, social behavior, neurologic disease, psychological disorders, and stress. Discussions of research in both animal models and human patient populations are included.